EFFECT OF SOAKING AND HYDROLYSIS TIME VARIATIONS ON GELATIN CHARACTERISTICS FROM COW BONES - Pattiasina, Priska Marisa; Trisunaryanti, Wega; Wijaya, Karna (Program Studi Pendidikan Kimia, FKIP, Universitas Pattimura (Chemistry Education Study Program, Faculty of Teacher Training and Educational Sciences, Pattimura University), 2025)
Gelatin extraction from cow bones has been conducted with variations in both acid and alkaline soaking. The gelatin extraction process from cow bones consists of two steps: soaking the cow bones and collagen hydrolysis. During the soaking step, continuous soaking was performed, beginning with soaking in a 4% NaOH alkaline solution, followed by acid soaking using a 1.2% citric acid solution, and further acid soaking with 4% HCl, with variations in soaking times of 1 hour, 12 hours, and 24 hours. The soaked cow bones were then hydrolyzed at temperatures of 60°C and 80°C for 5 hours. The resulting gelatin was characterized using FTIR and SDS-PAGE techniques. The best-characterized gelatin, with a band thickness in the molecular weight range of about 120 kDa, confirmed as the α chain, was obtained from soaking for 24 hours and hydrolyzing at 80°C.